2020
DOI: 10.1088/1742-6596/1686/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Helium accumulation in tungsten layers deposited in Ar-He magnetron discharge

Abstract: W-He co-deposition was studied by means of in-vacuo thermal desorption spectroscopy. W-He co-deposited layers were produced at substrate temperatures varied from 400 K to 800 K with a 50 K temperature step. It was found that the He content decreases from ∼1.7 at. % at 400 K to ∼0.17 at. % at 750 K. At 800 K, an increase in the He content was observed, that should be caused by significant changes in the film structure. Helium TDS spectra had two main peaks with maxima in the 500-600 K range and at ∼960 K; the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The slopes of the I -V characteristics in glow (repetitive mode) and arc (monopulse mode) are clearly different. Krat et al [21] have shown that the 'runaway' regime is not justified for the graphite-Ar HiPIMS discharges, even at high (but contained) current density. Indeed, the contribution to the discharge current is roughly half due to gas ions (Ar + ) and the other half to target ions (C + ), indicating a significant contribution of the gas recycling and the absence of runaway regime for C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slopes of the I -V characteristics in glow (repetitive mode) and arc (monopulse mode) are clearly different. Krat et al [21] have shown that the 'runaway' regime is not justified for the graphite-Ar HiPIMS discharges, even at high (but contained) current density. Indeed, the contribution to the discharge current is roughly half due to gas ions (Ar + ) and the other half to target ions (C + ), indicating a significant contribution of the gas recycling and the absence of runaway regime for C.…”
Section: Discussionmentioning
confidence: 99%
“…Other modes called 'non-sputtering' have been identified, in spite of the high discharge current (within 100-1000 A) under specific conditions [18,19]. Even if Ar is the gas most commonly used for magnetron sputtering discharges, the literature have shown specific interests for pure He [20], He mixed with Ar [21] or H 2 [22]. The latter mixtures aim to raise the pulse current, but the discharge often degenerates and arcs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works, carried out with pure Ne or Ar/Ne mixture [5][6][7], reported on the behavior of the discharge current, the gas recycling, and the final properties of deposited thin films. The literature has also shown specific interests for alternative gases like pure He [8], He mixed with Ar [9] or H 2 [10]. More specifically, high current densities (> 5A cm −2 ) [11] have been reported for pure helium, subject of the measurements presented in this paper.…”
mentioning
confidence: 84%
“…The results of helium influence on deuterium retention in co-deposited tungsten films were shown in [57]. For co-deposition W films a tungsten target was sputtered in a magnetron discharge in an Ar-D 2 -He mixture.…”
Section: Sequential and Simultaneous Implantations Of Deuterium And H...mentioning
confidence: 99%